2007
DOI: 10.1002/jat.1212
|View full text |Cite
|
Sign up to set email alerts
|

Antifibrotic effect of captopril and enalapril on paraquat‐induced lung fibrosis in rats

Abstract: Although different treatment modalities have been implemented for pulmonary fibrosis, the results have not been promising and these conditions have been considered untreatable and irreversible. Thus, a plethora of new drugs has been tried for the control of this condition in recent years. This study examined the effects of two angiotensin-converting enzyme inhibitors, captopril and enalapril, on paraquat-induced pulmonary fibrosis in rats, through biochemical and histopathological parameters. Male albino Wista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 44 publications
1
18
0
Order By: Relevance
“…Reduction of lipid peroxidation may contribute to its protective effect in lung tissue. Some studies aiming at using antioxidants such as melatonin, enalapril and captopril have demonstrated that these antioxidants could provide some prevention of the fibrogenic effect of paraquat (19,20). Our investigation of ambroxol is consistent with their conclusions.…”
Section: Discussionsupporting
confidence: 90%
“…Reduction of lipid peroxidation may contribute to its protective effect in lung tissue. Some studies aiming at using antioxidants such as melatonin, enalapril and captopril have demonstrated that these antioxidants could provide some prevention of the fibrogenic effect of paraquat (19,20). Our investigation of ambroxol is consistent with their conclusions.…”
Section: Discussionsupporting
confidence: 90%
“…Paraquat is known to induce toxicity in cells by stimulating oxygen utilization via redox cycling and the generation of reactive oxygen intermediates (10)(11)(12). However, the exact role of paraquat in the progression of pathogenesis has not been clearly established (13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…Yao et al investigated the anti-fibrotic effect of losartan and found that the protective effect of losartan may be associated with its antifree radicals and the reduction in TGF-β1 (23). The results of Ghazi-Khansari et al's work (24) showed that captopril and enalapril improved pulmonary fibrosis in histopathological studies as well as decreasing collagen content in the lung tissue. Marut et al's research (25) on irbesartan as an AT1 blocker indicated a protective effect of irbesartan by the inhibition of inflammation and NO production.…”
Section: Discussionmentioning
confidence: 99%